The Effect of Different Processing Methods on the Proximate Composition of Banded Gourami (Trichogaster fasciata) - Nanaobi, Hemam; Chungkham Sarojnalini; Daniel N.; Hawaibam Romharsha (Fishery Technology, 2023)
Fish is considered as an important component of the human diet owing to their rich nutritional profile, including high levels of proteins, n-3 polyunsaturated fatty acids, notably eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), along with various essential micronutrients, such as minerals and vitamins. The Food and Drug Administration (FDA) recommends fish for human nutrition, food security, and medicine. Prior research advocates that fish consumption on a regular basis minimizes the risks of heart related diseases, malnutrition, and nutritional deficiencies in humans (Kumar et al., 2022). Available literature further suggests that the consumption of fish two times a week noticeably improves human health as they are rich in the longchain polyunsaturated fatty acids, mainly omega-3 and omega-6 fatty acids that prevent the occurrence of many human diseases (Stansby, 1985; FAO, 2008; Tawfix, 2009; Lilly et al., 2017; Tilami & Sampels, 2018).